The Middle American species of Embates Chevrolat (Coleoptera: Curculionidae: Baridinae) - Prena, Jens (Zootaxa, 2005)
The neotropical weevil genus Embates Chevrolat is revised. New synonyms of Embates are Drepanambates Jekel, Batames Casey, Macrambates Casey and Cholinambates Casey. Information is provided about the morphology of the immature stages, life history, sexual dimorphism and morphological variability. A total of 69 species is recognized in Middle America, 38 of which are newly described here: E. aequiperabilis, E. aliquantulus, E. bicoctura, E. burgeri, E. callifer, E. chelys, E.clandestinus, E. consimilis, E. cordiger, E. crinipes, E. discissus, E. discordabilis, E. euchasma, E. euscheme, E. flavoplagiatus, E. galbinus, E. gilvopictus, E. gracilis, E. intermedius, E. kunicus, E. maculifer, E. marchionis, E. mendax, E. oculifer, E. paludicola, E. paucilimbatus, E. pauhans, E. peperomiae, E. politus, E. pseudobumbraticus, E. pullus, E. rutilus, E. sagittifolicus, E. scambus, E. subulirostris, E. terrabanicus, E. todillofasciatus and E. uniformis. Six new subspecies are described: E. polymorphus altrimsecus, E. polymorphus dotensis, E. polymorphus fortunensis, E. polymorphus tabulensis, E. polymorphus zeledonensis and E. leucopleura discolor. New combinations are E. belti (Champion), E. leucopleura (Champion) and E. flavolimbatus (Voss) [all from Drepanambates]. New synonyms are E. belti [= E. triangularis (Champion)], E. fasciolatus (Chevrolat) [= E. sexpunctatus (Champion)] and E. solani (Champion) [= E. divisus (Casey)]. Embates rugosus (Hustache) is distinguished from E. solani and resurrected as a valid species. New records for Middle America are E. flavolimbatus (Voss), E. justini (Chevrolat) and E. rugosus. Descriptions, line drawings of habitus and male genitalia, geographic distributions, plant associations and keys for identification are provided.